The social dimensions of an incentive-based urban recycling program: a case-study from Istanbul, Turkey - AKPINAR, AYDIN; GÜRSOY HAKSEVENLER, BETÜL HANDE (My University, 2023)
Incentive-based programs are increasingly becoming common in recycling promotion. These programs are usually designed on the premise that the incentives will nudge the participants’ behavior to be more pro-recycling so that they may continue to support recycling even if there is no reward presented anymore. The technical and economic aspects receive a great deal of attention, while the social elements do not usually receive the same level of attention as above. In this study, a survey was conducted to recognize the recycling consciousness of participants in an urban recycling promotional program. The urban recycling program analyzed in this study was administered by Zeytinburnu Municipality in Istanbul, Turkey. This program had about 10,000 active users at the time of this face-to-face survey conducted among 428 participants in 2021. Zeytinburnu is a densely populated municipality, with a greater majority residing in apartment buildings. The results revealed that about half of the survey population was spontaneous recyclers, and they would like to continue even if there was no reward, while the other half was in the program just for the reward. However, the findings also displayed the potential of the incentive mechanism to be used to enhance the pro-recycling behavior of its participants. This may be achieved through educational tools and providing solutions to ease the burden most apartment-dwelling participants carry with storage/transportation issues.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Kamu Yönetimi; Kentleşme ve Çevre Sorunları; Çevre Mühendisliği; Çevre Bilimleri; Mühendislik ve Teknoloji; Social Sciences and Humanities; Political Science; Public Administration; Urbanization and Environmental Problems; Environmental Engineering; Environmental Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Çevre / Ekoloji; Sosyal Bilimler Genel; ÇEVRE BİLİMLERİ; KAMU YÖNETİMİ; SİYASET BİLİMİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENVIRONMENT/ECOLOGY; SOCIAL SCIENCES, GENERAL; ENVIRONMENTAL SCIENCES; PUBLIC ADMINISTRATION; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Yaşam Bilimleri; Political Science and International Relations; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Social Sciences & Humanities; Life Sciences; recycling; source separation; waste collection; incentives; recycle consciousness; waste management in municipalities